2013
DOI: 10.1016/j.gene.2013.04.051
|View full text |Cite
|
Sign up to set email alerts
|

A 914-bp promoter is sufficient to reproduce the endogenous prolyl oligopeptidase gene localization in the mouse placenta if not subject to position effect

Abstract: Prolyl oligopeptidase (POP) is a widely distributed multifunctional protein which has an endopeptidase activity to cleave a -Pro-X- peptide bond. In spite of numerous studies about POP, the mechanism by which its transcription is controlled has not been well investigated. Here we generated transgenic mice bearing a transgene which contained a 914-bp POP gene promoter linked to the enhanced green fluorescent protein (EGFP) gene to assess the in vivo promoter activity. We established six transgenic lines with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…POP could control Ascl2 by changing the phosphorylation status of proteins in these pathways, as it has been reported to regulate protein phosphorylation (Williams et al 1999; Duan et al 2014). It is interesting that Ascl2 is activated by a placenta-specific transcription factor, AP-2γ (Sharma et al 2016), and POP is also suggested to be controlled by AP-2γ (Matsubara et al 2013). SpT differentiation may be regulated by an AP-2γ–POP–Ascl2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…POP could control Ascl2 by changing the phosphorylation status of proteins in these pathways, as it has been reported to regulate protein phosphorylation (Williams et al 1999; Duan et al 2014). It is interesting that Ascl2 is activated by a placenta-specific transcription factor, AP-2γ (Sharma et al 2016), and POP is also suggested to be controlled by AP-2γ (Matsubara et al 2013). SpT differentiation may be regulated by an AP-2γ–POP–Ascl2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…6.1k-POPpr-Luc: A 914-bp mouse prolyl oligopeptidase (POP) gene promoter was subcloned into a pEGFP-1 vector (Clontech) (47,48). The plasmid was digested with BamHI and EcoRI, and the POP promoter was purified, blunted, and inserted into 6.1k-Luc which was digested with EcoRV and Tth111I and blunted.…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…Then, we replaced most of the lncRNA-Amhr2 sequence with torazame ER cDNA which was similar in length (6.1k-toER-Luc) (46), and the lncRNA-Amhr2 promoter sequence with the POP promoter (6.1k-POPpr-Luc). The replacement with torazame ER would result in transcription of a sequence unrelated to lncRNA-Amhr2, and the POP promoter was known to show strong promoter activity in various types of cells and expected to drive lncRNA-Amhr2 transcription at a higher level than other constructs (47,48,51). As controls, we also prepared the constructs that contained the 0.5-kb Amhr2 promoter (0.5k-Luc) and lacked a lncRNA-Amhr2 promoter sequence (6.1k-∆lncPr-Luc).…”
Section: Lncrna-amhr2 Activation Increases Amhr2 Promoter Activity Inmentioning
confidence: 99%